Posibilidades de controlar Liriomyza munda Frick con insecticidas organofosforados - Hoffmann, H.; Masso, E.; Herrera, A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The insecticides demephion, diazinon, dimethoate, fenitrothion, methidathion, omethoate, oxydemeton-methyl, parathion-methyl, phosphamidon, vamidothion, disulfoton, and IPSP were tested for the control of Liriomyza munda in potatoes in Cuba Disulfoton and IPSP were applied as granular formulations at two dosage rates at potato planting. The other insecticides were sprayed at weekly and fortnightly intervals. Disulfoton and IPSP were applied as granular formulations at two dosage rates at insecticides were inadequately effective at the applied concentration. On the other hand, dimethoate sprayed weekly at a concentration of 0.05 per cent a.i and a volume of 600 litres per hectare was very effective. Omethoate sprayed at the same concentration gave a still better effect. In fact, a good level of control is obtainable with omethoate also when it is sprayed at two-week intervals.